Pembuatan Sistem Informasi dengan Analisis dan Perancangan Berorientasi Objek - Pelawi, Dewan (ComTech: Computer, Mathematics and Engineering Applications, 2013)
To generate an information system which is in accordance with the needs of company requires an analysis of business processes by observing the running system. Solutions for problems found when doing the business are observed using the systems approach. Object-oriented analysis and design is a method currently used to build an information system. The system development with "Object Oriented Analysis & Design (OOAD)" method stated by Satzinger includes making activity diagram, event table, class diagram, usecase diagrams, usecase description, state chart diagram, deployment and software architecture, first-cut design class diagram, simple sequence diagram (SSD), the sequence diagram (first-cut, view layer, data access layer), communication diagram, updated design class diagram, package diagram, persistent object, user interface. The result obtained after performing all phases is an information system that fits the company needs which is expected to improve the performance and effectiveness in business processes and also support the company's business goals.